Dampak Game Online terhadap Motivasi Belajar dan Keterampilan Komunikasi Interpersonal Mahasiswa Fakultas Ilmu Komunikasi Universitas Sumatera Selatan - Lovia Evanne; Adli Adli; Ngalimun Ngalimun (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
Communication is a social event that occurs when a human interacts with other humans. The assumptions that there is motivation to learn can be seen with the achievements and cognitive perspectives of students, both elementary school students or college students. The problem of learning motivation in students today is increasingly complex, including online game opium which develops in the dynamics of our society, especiallyIndonesia. This research method is descriptive qualitative. Based on the results of the study it can be concluded (1) There is a positive impact of playing online games on learning motivation. Can be seen from the efforts to increase learning motivation. The cumulative grade point average (GPA) is very satisfying to perfect. (2) There is a positive impact of online games on interpersonal communication skills. Can be seen from the interaction between players in the online game play. Online media-based interpersonal interaction and communication, online games. (3) There is a positive impact of playing online games on learning motivation and interpersonal communication skills. Students who like to play online games have motivation to go to college. This can be seen from the cumulative achievement index (GPA) which is very satisfying to perfect. These students can interact, socialize and communicate well through online game media.